Tumor mass in the lung with superior vena cava syndrome - Petrović-Majstorović Tatjana; Juković Mirela; Vujasinović Gordana; Dragišić Dragan; Petrović Nemanja (Archive of Oncology, 2022)
Group of symptoms due to vena cava superior obstruction is named superior vena cava syndrome. A 65-year-old female, long-standing smoker was presented with a two-week history of dry cough and facial swelling. The patient noticed a palpable mass on the right side of the neck. Computer tomography scan with contrast showed extensive, irregular, non-homogenous consolidation in the right upper lobe, involving the right hilus, surrounding the aortic arch, supra aortic branches and pleural effusion at the right side of the body. Also, ultrasound examination of supra clavicular space showed enlarged pathologic hypoehogenic lymph node without an echogenic hilum. Ultrasound guided fine needle biopsy of lymph node was performed, and cytopathology findings showed metastatic lesion from primary microcellular lung cancer, IIIC stadium, cT4N3M0. Venous angioplasty was performed showing stenosis in the superior vena cava. After balloon dilatation, the stent was placed at the site of stenosis. The patient received chemio and radiotherapy and survival time was seven months. Superior vena cava syndrome is an urgent clinical condition, and lung cancer is the leading cause of this syndrome. Computer tomography imaging findings and endovascular stent placement are important for detection and management of the superior vena cava thrombosis.